Kenaf fiber composites: a review on synthetic and biodegradable polymer matrix - Dulina Tholibon,; Izdihar Tharazi,; Abu Bakar Sulong,; Norhamidi Muhamad,; Nur Farhani Ismail,; Mohd Khairul Fadzly Md Radzi,; Nabilah Afiqah Mohd Radzuan,; Hui, David (Penerbit Universiti Kebangsaan Malaysia, 2019)
This review paper deals with the previous and current works published on the kenaf fiber composites. Kenaf is grown commercially in South East Asia country and widely used in the construction and infrastructure as well as in the automotive industry. Kenaf fiber is usually reinforced with synthetic based polymer resin such as polypropylene. However, recent studies tend to concern towards the environmental issues which kenaf fiber act as an alternative natural fiber competitor. Moreover, the combination of the natural fiber and the biodegradable polymer able to reduce the negative impact on human health. Hence, researcher-initiated the interest focusing on the biodegradable materials obtained from the renewable sources. A huge attention gave to the kenaf fiber reinforced bio-polymer materials such as polylactic acid. The processing technique and the fiber orientation within the composite materials are discussed extensively in order to obtain the maximum composite performance. Results indicated that the mechanical properties; tensile strength and tensile modulus, are improved as the kenaf fiber was aligned in uni-direction. Therefore, this paper overview on the kenaf retting types in the common form of kenaf fibers and discussing the thermoplastic polymer matrices types used in the fabrication processes. In addition, the challenging of using kenaf fibers composites and its application in the automotive industry also highlighted.